The Impact of Teachers' Welfare Package on Teachers' Job Satisfaction - Ahmed Oluwatobi Adekunle (International Journal of Social Science and Religion (IJSSR), 2025)
The critical role of education in national development is widely acknowledged, with the 2016 UNESCO recommendation on the status of teachers highlighting its significance. The quality of education, encompassing both learning and character development, is a central goal for every country's educational system. Globally, welfare programs are crucial in enhancing teachers' job performance and motivating teaching activities. This study examines the impact of teachers' welfare packages on job satisfaction in Edo State, Nigeria. The sample includes 80 respondents from eight secondary schools. A questionnaire was administered to collect data, which was analyzed using chi-square analysis. The findings suggest that teachers' welfare packages positively influence job satisfaction in Edo State. The study recommends strengthening government policies to ensure teachers are better supported, encouraging them to engage in their teaching roles for improved learning outcomes fully.